The impact of stigma on mental health and quality of life of infertile women: A systematic review - Xie, Yue; Ren, Yue; Niu, Changmin; Zheng, Ying; Yu, Ping; Li, Lin (Frontiers in Psychology, 2023)
Introduction The stigma of not giving birth to children affects approximately 53. 08~64% of female infertility patients worldwide. This stigma not only causes harm to the mental health of these infertility patients, but also affects their quality of life, making them bear the adverse social consequences such as domestic violence, marriage breakdown, or even delay in receiving the treatment. Therefore, it is crucial to have a deep understanding of the patients' stigma and effective intervention in alleviating it. Aims/Question This study aims to discuss and summarize the stigma in infertile women and its impact on patients, and to provide a theoretical basis for the clinical treatment and nursing intervention of disease stigma in infertile female patients. Methods The literature search used four English databases (Cochrane Library, EMBASE, Web of Science, and PubMed) and two Chinese databases (CNKI and Wanfang). The search time of the literature ranges from the establishment of the library to 2022, with no language restriction. Results The review included 28 studies, with 20 cross-sectional studies and 8 qualitative studies. This study found that social support, living environment, education level, occupation, and fertility awareness were the major influencing factors of infertility stigma. Conclusions Infertility stigma can bring heavy mental pressure and psychological burden to female infertility patients and affect their quality of life. Therefore, effective and targeted psychological interventions should be developed to reduce the patients' stigma and improve their quality of life. Implications for practice Healthcare workers must develop targeted nursing interventions, provide professional counseling services to reduce the level of stigma in female infertility patients, alleviate fertility stress, and improve their quality of life.